Assessment of coxofemoral joint laxity in juvenile boerboel dogs using mobile phone goniometry - Kitshoff, Adriaan (University of Pretoria, 2025)
Dissertation (MMedVet (Small Animal Surgery))--University of Pretoria, 2024.